A novel testis ubiquitin-binding protein gene arose by exon shuffling in hominoids - Babushok, Daria V.; Ohshima, Kazuhiko; Ostertag, Eric M.; Chen, Xinsheng; Wang, Yanfeng; Mandal, Prabhat K.; Okada, Norihiro; Abrams, Charles S.; Kazazian, Haig H. (Genome Research, 2007)
Most new genes arise by duplication of existing gene structures, after which relaxed selection on the new copy frequently leads to mutational inactivation of the duplicate; only rarely will a new gene with modified function emerge. Here we describe a unique mechanism of gene creation, whereby new combinations of functional domains are assembled at the RNA level from distinct genes, and the resulting chimera is then reverse transcribed and integrated into the genome by the L1 retrotransposon. We characterized a novel gene, which we termed PIP5K1A and PSMD4-like (PIPSL), created by this mechanism from an intergenic transcript between the phosphatidylinositol-4-phosphate 5-kinase (PIP5K1A) and the 26S proteasome subunit (PSMD4) genes in a hominoid ancestor. PIPSL is transcribed specifically in the testis both in humans and chimpanzees, and is post-transcriptionally repressed by independent mechanisms in these primate lineages. The PIPSL gene encodes a chimeric protein combining the lipid kinase domain of PIP5K1A and the ubiquitin-binding motifs of PSMD4. Strong positive selection on PIPSL led to its rapid divergence from the parental genes PIP5K1A and PSMD4, forming a chimeric protein with a distinct cellular localization and minimal lipid kinase activity, but significant affinity for cellular ubiquitinated proteins. PIPSL is a tightly regulated, testis-specific novel ubiquitin-binding protein formed by an unusual exon-shuffling mechanism in hominoid primates and represents a key example of rapid evolution of a testis-specific gene.
10.1101/gr.6252107